Bangladesh Alive & Thrive Process Evaluation Survey 2013: Pushti Kormi (PK) - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the frontline health worker (FLW) survey conducted to gather data for a process evaluation as a part of an impact evaluation study of Alive & Thrive (A&T) interventions delivered through Building Resources Across Communities' (BRAC) Essential Health Care (EHC) Program in Bangladesh. The objective of the impact evaluation study is to evaluate the synergistic impact of the A&T community component along with media communications and private sector activities such as the promotion and integration of micronutrient powders. A&T is a six-year initiative to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. In Bangladesh, A&T is working with the government, nongovernmental organizations, and private initiatives to support the implementation of the National IYCF Strategy and Action Plan. The BRAC organization is delivering A&T’s community interventions within its EHC Program and its Maternal, Neonatal, and Child Health (MNCH) Program. BRAC’s frontline health workers, known as Shasthya Shebika and Shasthya Kormi, delivered age-appropriate IYCF counseling and support services during home visits, antenatal and postnatal sessions, and health forums. The process evaluation survey conducted as part of the impact evaluation of A&T interventions delivered through BRAC’s EHC platform had two components—(i) household survey, and (ii) frontline health workers survey. The household survey captured the main impact indicators for A&T (WHO-recommended IYCF indicators and child anthropometry), use and exposure to A&T’s intervention platforms, and a variety of other data related to the use of the interventions. This included data on caregiver knowledge and perceptions about IYCF practices, challenges experienced in relation to IYCF practices, caregiver resources (such as education, childcare knowledge, and experience, and physical and mental health) and household resources (such as household composition, socioeconomic status, and food security). The frontline health worker survey gathered data on service provision by BRAC frontline health workers, traditional birth attendants (TBA), and village doctors. Data were also gathered on health worker time commitment, knowledge and attitude and training related to IYCF, complementary feeding, sanitation and hygiene practices, and their job supervision and contact with other workers; their knowledge and skills about Pustikona. Three questionnaires were developed for frontline health workers survey—(i) Shasthya Shebika (SS) questionnaire, (ii) Shasthya Kormi (SK) questionnaire, and (iii) Pushti Kormi questionnaire. The data included here are from the survey of Pushti Kormi. The survey was conducted in the 25 upazilas across 13 districts in Bangladesh between April and August 2013 by the IFPRI team in collaboration with Data Analysis and Technical Assistance, Ltd. (DATA).